The sisters of Auschwitz : the true story of two Jewish sisters' resistance in the heart of Nazi territory - Iperen, Roxane van (Harper, 2021)
During the Second World War two Jewish sisters -- Janny and Lien Brilleslijper -- run one of the largest hideaways in The Netherlands: The High Nest, a villa in The Gooi area. While the last remaining Jews are being hunted in The Netherlands, the lives of dozens of hideaways kept going for better or for worse, right under the noses of their National Socialist neighbours. Eventually, the nest is exposed and the Brilleslijper family put on one of the last transports to Auschwitz, along with the (Anne) Frank family. Roxane's novelistic eye combined with her rigorous research result in a hugely compelling portrayal of courage, treason and human resilience.